Glucocorticoid receptor gene variants and lower expression of NR3C1 are associated with cocaine use. (15th May 2018) - Schote, Andrea B.; Jäger, Kristina; Kroll, Sara L.; Vonmoos, Matthias; Hulka, Lea M.; Preller, Katrin H.; Meyer, Jobst; Grünblatt, Edna; Quednow, Boris B.
Abstract: Animal and cross‐sectional human studies suggest that chronic cocaine use is associated with altered responsivity of the hypothalamic–pituitary–adrenal axis to stress. Moreover, increased susceptibility to stress has been proposed as an important factor for development, maintenance and relapse of cocaine addiction. As the glucocorticoid receptor gene ( NR3C1 ) mediates genomic effects of the stress hormone cortisol, we investigated NR3C1 expression and the association of NR3C1 genotypes with cocaine use, addiction and comorbid psychiatric symptoms in 126 chronic cocaine users and 98 stimulant‐naïve healthy controls. A comprehensive psychiatric assessment was performed including severity of depressive symptoms and current psychological distress. Whole blood NR3C1 mRNA levels were determined and six NR3C1 polymorphisms (rs10482605, rs41423247, rs10052957, rs6189, rs56149945 and rs6198) were genotyped. Compared to controls, cocaine users showed significantly lower NR3C1 expression ( P  < 0.001), which was not affected by NR3C1 genotypes. In controls, rs41423247 [ P <  0.01, false discovery rate (FDR)‐corrected], haplotype 2 and haplotype 3 (both P  < 0.05, FDR‐corrected) were associated with altered NR3C1 gene expression. Haplotype 3 (including minor alleles of rs10052957 and rs41423247) was associated with an increased risk for cocaine addiction (odds ratio = 2.74, P  < 0.05, uncorrected). Moreover, addicted cocaine users carrying haplotype 3 showed higher depression scores ( P <  0.01, FDR‐corrected) than noncarriers. Considering possible confounding effects of alcohol and/or depression, we conclude that chronic cocaine use is associated with lower NR3C1 gene expression suggesting possible direct effects of the drug on the biological adaptation of stress‐related genes. Finally, we postulate that haplotype 3 of NR3C1 might serve as a potential risk factor for stimulant addiction and associated psychiatric symptoms. Abstract : We found a significant lower NR3C1 expression in cocaine users (CUs) compared to with stimulant‐naïve healthy controls. In the control group, NR3C1 rs41423247 genotype and related haplotypes modulated NR3C1 expression, whereas this effect was not present in CUs. In severe CUs, an increased risk for cocaine addiction as well as for depression was associated with NR3C1 haplotype 3. We propose possible direct effects of cocaine on the biological adaptation of stress‐related genes and postulate haplotype 3 as potential risk factor.